The Initiative of Forensic Specialists on Organ Transplantation of Brain Death Legal Cases - Bilgin, Nursel Gamsız; Dokgöz, Halis; Kar, Hakan (The Bulletin of Legal Medicine, 2009)
We aimed to discuss organ transplantation of brain death legal cases due to high benefits of patient with forensic and legal points of view. Case: 16 years old, entubated male patient who was intoxicated from inhalation of bottled gas with unconsciousness, bilateral fix-dilated pupils and GCS:3 was admitted to Mersin University Faculty of Medicine and hospitalized in intensive care unit. Subarachnoidal hemarrogie and brain edema were detected in Computerized Cerebral Tomograpy and given medical teraphy. But there was no answer to the treathment and the family was given consent of organ transplantation. Brain death was occured in 04.18.2007 and the case is consulted with our Department of Forensic Medicine. After discussing the case with public attorney we concluded that the organs which was planned to be transplantated had no influence on cause of death and the medicolegal autopsy can performed after transplantation operation. The public attorney approved the procedure and the medicolegal autopsy was performed after operation. There are serious problems in organ transplantation for legal cases. Sheduling of legal notification and pastmortem examination is not clear in such cases. It’s not obvious that these procedures must before or after transplantation operation. The article 11 of the law code numbered 2238 describes the priority of urgent transplantation for patient survive due to the principle of high benefits of the patient. The legal cases who becomes doneur for organ tranplantation must be consulted and evaluated with Forensic Medicine Departments. Key words: Brain death, organ transplantation, legal case